Physicochemical characterization and nutritional composition analysis of pineapple guava at three different ripening stages (2016)
Pineapple guava (Acca sellowiana [O. Berg] Burret) is a fruit with export and production potential in Colombia. However, there are few reports about its composition concerning physiological behavior throughout the different ripening phases. Intending to confront this situation, a study was proposed in order to evaluate the physicochemical properties and the nutritional composition of pineapple guava fruits in three different phases of ripening, determined by the weeks elapsed after anthesis, considering it undeveloped for week 17 (W17), ripe for week 20 (W20) and overripe from week 21 (W21). Pineapple guava fruits were preliminarily characterized, they underwent a bromatological analysis and their content of vitamin A and C content was established. The results showed a significant content of crude fiber and total carbohydrates in the three evaluated phases. There was also a decrease in the neutral detergent fiber of 38% between W17 and W21. The highest level of vitamin C was reported in W17 (67.82 mg ascorbic acid/g dry sample), as well as for vitamin A (12.65 mg β-carotene/g dry sample). In a physical-chemical characterization, the existence of a particular physiological behavior is possible because of the development in size and mass of the fruit after physiological ripening. Additionally, the calcium and reducing carbohydrate content can be associated with the pulp browning phenomenon. Clearly, pineapple guava is a promising fruit thanks to its nutritional properties, according to the current consumption tendencies.